Life Satisfaction and Suicidal Ideation Among Chinese College Students During the Recurrent Outbreak of COVID-19: A Moderated Mediation Model - Yu, Zhijun; Liu, Haidong; Ye, Baojuan; Tang, Chunyan; Huang, Dawu; Liu, Lu (Frontiers in Psychiatry, 2022)
The present study examined a moderated mediation model between life satisfaction and suicidal ideation among Chinese college students during the recurrent outbreak of COVID-19. Seven hundred and ninety college students participated in the study and completed questionnaires on life satisfaction, suicidal ideation, depression, and gratitude. Findings indicated that (1) Depression played a partial mediating role between life satisfaction and suicidal ideation. Life satisfaction was not only directly affected suicidal ideation, but also indirectly affected suicidal ideation through the mediating effect of college students' depression; (2) Gratitude played a moderating role in the effect of life satisfaction on depression, and the link between life satisfaction and suicide ideation was only significant for those with higher gratitude. This study provides practical implications for the prevention of suicidal behavior among Chinese college students during the recurrent outbreak of COVID-19.